Evaluation of Air Quality based on Air Quality Index in Kerman City, 2015 - Mohsen heidari; zoha heidarinejad; Vali Alipour; kavoos dindarloo; Omid Rahmanian; Babak Goodarzi; hasan Mousapour (Mashhad University of Medical Sciences, 2017)
Background: Air pollution and its health effects is a principal challenge in Iran. One of the effective measures to control air quality is to determine the actual amount of pollutants and describe the air quality in comparison with standard conditions. The main objective of this study was to evaluate the air quality in Kerman based on Air Quality Index (AQI) and to determine the responsible pollutant in polluted days during April 2015 to March 2016. Materials and Methods: In this cross-sectional study, the air pollutants concentration data were obtained from Kerman environmental protection agency. Then, the AQI values were calculated based on the levels of the criteria pollutants, i.e., CO, NO2, SO2, PM10, PM2.5 and O3. Based on AQI levels, the air quality was classified into six groups including good, moderate, unhealthy for the sensitive people, unhealthy, very unhealthy and dangerous. Results: During the studied year, the air quality in 7%, 60%, 29% and 4% of the days, in which the pollutants concentrations were measured, was in clean condition, healthy conditions, unhealthy conditions for sensitive groups and unhealthy condition, respectively. The best and worst air quality conditions were observed in January (in cold season) and April (in warm season), respectively. PM2.5 was the responsible pollutant for air pollution in Kerman. Conclusion: The results showed that the main responsible pollutant which causes air pollution in Kerman was particulate matter. This situation may be originated from the local and regional dust storms, especially from south-west and Sistan regions. Therefore, the essential actions must be taken to control such pollution and to minimize the community exposure to this pollutant.